Comportamento termorregulatório e alimentação em Iguana iguana (Squamata, Iguanidae) - Viola, Matheus Fernandes [UNIFESP] (2015)
Few environmental factors exert so much influence on the physiology of animals as temperature. Each activity carried out by an animal occurs in a range of body temperatures that is physiologically appropriate. Some reptiles select high temperatures after feeding or spend more time basking. Approximately 30-40% of energy requirements of the green iguana (Iguana iguana) is provided by fermentation of food, which is facilitated when these animals are put under the sun and keep body temperature above 30°C. Thus, it is possible that food intake in those animals can bring them to change their thermoregulatory behavior to search for more suitable temperatures. In this sense this work intends to investigate how changes in the external temperature affect the energy efficiency of absorption of these animals and also if the intake and the quality of food eaten by I. iguana results in changes in thermoregulatory pattern. Briefly, the animals showed digesta transit time (TT) and lower food consumption (FC) at high temperatures, in comparison with the low temperature regime. There were no differences between the apparent digestive efficiency (ADE) between the high temperature treatments and lower temperatures. The mean internal body temperatures, maximum internal temperatures and third thermal quartile were in general higher in fed iguanas than fasting group when the thermal environment allowed the choice. In this work we showed that the correlations between ambient temperature, energy absorbing efficiency and feeding of Iguana iguana. The searching for warmer environments after feeding period will provide greater internal body temperatures that facilitate energy absorption. When the thermal environment does not provide ideal temperatures, a thermal restriction on the choice of "preferred" temperatures leads to a lower internal body temperature that depress the energy absorption.